Application of central composite design for optimization of microbial growth inhibition using pineapple leaves juice - Amirah, Ya’acob; Norazwina, Zainol (IOP Publishing, 2020)
Microbial growth inhibitor is very important to prevent transmission of disease and infection. In this research paper, pineapple (Ananas comosus) leaves juice (PLJ) was used as microbial growth inhibitor agent. Microbe from infected pineapple leaves was used as microbe model. The selected factors in this study were temperature and microbial inhibition time with the range between 35 to 39 °C and 10 to 50 minutes respectively. In order to determine the optimum condition for microbial growth inhibition process, an experiment were designed according to a central composite design (CCD) in two variables following the response surface methodology (RSM). Microbial growth inhibition was measured from cell dry weight of microbe using dry weight measurement method. Result from RSM showed that microbial inhibition time have significant effect on the microbial growth inhibition. Model validation from experiments showed good correspondence between experimental and predicted values. The highest error was achieved at 8.03%. The optimal condition obtained for microbial growth inhibition was at 37 °C and 34.25 minutes. Minimum cell dry weight was found at 0.0508 gram which indicated the microbial growth inhibition at 94.73%. Optimal condition from this study would be useful for the application of PLJ in pineapple plantation.